User acceptance of 360-degree video news: an integrated model of extended TAM and U&G perspectives. Issue 4 (2nd October 2022) - Kim, Yunju; Lee, Heejun
ABSTRACT: Adopting a uses and gratifications (U&G) approach, this study identified user motivations for watching 360-degree video news: pursuit of entertaining information, social conformity, and pursuit of usefulness. The current study also proposes a model that captures key antecedents and consequences of audiences' motives for consuming 360-degree video news by extending the technology acceptance model (TAM). Among the three motives for watching 360-degree video news, pursuit of entertaining information and pursuit of usefulness both significantly influence audience attitudes towards 360-degree video news. This is because of the perceived usefulness of the medium. Implications for research and practice are discussed.